Mathematical modelling of oscillations and wake waves in plasma - Chizhonkov, E. V. (Evgeniĭ Vladimirovich) (Boca Raton : CRC Press, Taylor & Francis Group, 2019)
This book is devoted to research in the actual field of mathematical modeling in modern problems of plasma physics associated with vibrations and wake waves excited by a short high-power laser pulse. The author explores the hydrodynamic model of the wake wave in detail and from different points of view, within the framework of its regular propagation, a development suitable for accelerating electrons, and the final tipping effect resulting in unregulated energy transfer to plasma particles. Key selling features: Presents research directly related to the propagation of super-power short laser pulses (subject of the 2018 Nobel Prize in Physics). Presents mathematical modeling of plasma physics associated with vibrations and wake waves excited by a short high-power laser pulse. Includes studies of large-amplitude plasma oscillations. Most of the presented results are of original nature and have not appeared in the domestic and foreign scientific literature Written at a level accessible for researchers, academia, and engineers.
OCLC-licensed vendor bibliographic record.
Keywords: Plasma oscillations -- Mathematical models; Plasma waves -- Mathematical models; Oscillations -- Mathematical models; Plasma (Ionized gases); SCIENCE / Energy; SCIENCE / Mechanics / General; SCIENCE / Physics / General; SCIENCE / Chemistry / General; SCIENCE / Mathematical Physics; SCIENCE / Physics